(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2023)
Accumulation of soil carbonates in the soil profile occurs mainly during the evaporation of mineralized groundwater in the modern hydromorphic stage of soil formation, and not during soil formation. assortment of plant residues. The increase in organic carbon in irrigated soils is associated with an increase in the recency of development and cultivation.